Animal Crossing and COVID-19: A Qualitative Study Examining How Video Games Satisfy Basic Psychological Needs During the Pandemic - Yee, Andrew Z. H.; Sng, Jeremy R. H. (Frontiers in Psychology, 2022)
The Covid-19 pandemic has affected the way many people live their lives. The increasing amount of time spent indoors and isolated during periods of lockdown has been accompanied by an increase in the time people spend playing video games. One such game which soared in popularity during the early stages of the pandemic was Animal Crossing: New Horizons. Through semi-structured interviews with players from different parts of the world, and using a theory-informed qualitative analysis, we document and examine players' motivations and experiences playing Animal Crossing: New Horizons during the pandemic. Findings suggest that playing the game helped satisfy various psychological needs – autonomy, relatedness, and competence – as described by Self-Determination Theory. Conversely, players stopped playing the game when they found that their psychological needs were thwarted or better met through other activities. Our findings offer support that video games can offer psychological relief in stressful contexts by providing opportunities for people to satisfy key psychological needs. Theoretical and practical implications are discussed.